The relationships among turnover intentions, professional commitment, and job satisfaction of hospital nurses - Lu, Kuei-Yun; Lin, Pi-Li; Wu, Chiung-Man; Hsieh, Ya-Lung; Chang, Yong-Yuan (Journal of professional nursing, 2002)
This study investigated the relationships among turnover intentions, professional commitment, and job satisfaction of registered nurses. A structured, self-administered questionnaire, including the Professional Commitment Scale, job satisfaction, turnover intentions, and demographic data, was distributed to 2,550 registered nurses. A total of 2,197 subjects completed the questionnaires with an 86.2 per cent response rate. All of the subjects were women. The mean age was 28.56 years. Seventy-two per cent of respondents had graduated with an associate's degree and 59 per cent were unmarried. There was a positive correlation between job satisfaction and professional commitment, intention to leave the organization, and between intention to leave the profession. The negative correlation was significant between professional commitment and turnover intentions, and between job satisfaction and turnover intentions. The discriminant analysis showed that 38.4 per cent of job satisfaction was correctly classified in predicting intention to leave the organization, and 30.5 per cent in predicting the intention to leave the profession. Thirty per cent of professional commitment was correctly classified in predicting intention to leave the organization, and 39.7 per cent in predicting the intention to leave the profession. The study suggests that there were different moderators that affect different turnover intentions of staff nurses. J Prof Nurs 18:214-219, 2002. Copyright 2002, Elsevier Science (USA). All rights reserved.